Potential Implications of Rimonabant on Age-Related Oxidative Stress and Inflammation - Renáta Szabó; Zsuzsanna Szabó; Denise Börzsei; Alexandra Hoffmann; Zelma Nadin Lesi; Patrícia Pálszabó; Andrea Pálszabó; Szabolcs Dvorácskó; Rudolf Gesztelyi; Krisztina Kupai; Dániel Priksz; Béla Juhász; et al. (MDPI AG, 2022)
Over the last decades, growing interest has turned to preventive and therapeutic approaches for achieving successful aging. Oxidative stress and inflammation are fundamental features of cardiovascular diseases; therefore, potential targets of them can improve cardiac outcomes. Our study aimed to examine the involvement of the endocannabinoid system, especially the CB1 receptor blockade, on inflammatory and oxidant/antioxidant processes. Twenty-month-old female and male Wistar rats were divided into rimonabant-treated and aging control (untreated) groups. Rimonabant, a selective CB1 receptor antagonist, was administered at the dose of 1 mg/kg/day intraperitoneally for 2 weeks. Cardiac amounts of ROS, the antioxidant glutathione and superoxide dismutase (SOD), and the activity and concentration of the heme oxygenase (HO) enzyme were detected. Among inflammatory parameters, nuclear factor-kappa B (NF-κB), tumor necrosis factor-alpha (TNF-α), and myeloperoxidase (MPO) enzyme activity were measured. Two weeks of low dose rimonabant treatment significantly reduced the cardiac ROS via boosting of the antioxidant defense mechanisms as regards the HO system, and the SOD and glutathione content. Consistently, the age-related inflammatory response was alleviated. Rimonabant-treated animals showed significantly decreased NF-κB, TNF-α, and MPO levels. Our findings prove the beneficial involvement of CB1 receptor blocker rimonabant on inflammatory and oxidative damages to the aging heart.